Childhood Health and Labor Market Outcomes in the Case of Type 1 Diabetes - Sofie Persson; Gisela Dahlquist; Ulf-G. Gerdtham; Katarina Steen Carlsson (Lund University, School of Economics and Management, Department of Economics, 2014)
This study investigates the impact of childhood health on labor market outcomes. We used type 1 diabetes as an instrument of health because its cause is multifactorial and it is triggered by a complex combination of genetic and environmental components; its incidence is low and unforeseeable for the individual; and its onset may be considered an exogenous health shock. Using data from the Swedish Childhood Diabetes Register and national registers on education, employment, and earnings for 2,485 individuals born in 1972–1978 and diagnosed with type 1 diabetes at <15 years old, we found that childhood health impacts on labor market outcomes. The results also imply that causality in the often observed correlation between health and socioeconomic status is partly explained by a gradient that runs from health to earnings, rather than the other way around, which has important implications for policy to reduce socioeconomic-related health inequality.
Keywords: I00; I10; I14; J01; 330; Health; chronic disease; earnings; employment; education